2011
DOI: 10.1007/s12257-011-0224-2
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of a sulfated galactan extracted from the marine alga Chaetomorpha aerea against Staphylococcus aureus

Abstract: The in vitro antimicrobial activity of the marine green algae Chaetomorpha aerea was investigated against gram-positive bacteria, gram-negative bacteria, and a fungus. The water-soluble extract of algae was composed of a sulfated (6.3%) galactan with a molecular weight of 1.160 × 10 6 Da and a global composition close to commercial polysaccharides, such as dextran sulfate or fucoidan. The polysaccharide was composed of 18% arabinose, 24% glucose, and 58% galactose. The re-suspended extracts (methanol, water) e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(42 citation statements)
references
References 30 publications
0
42
0
Order By: Relevance
“…Similarly, Pierre et al, (2011) also reported the antimicrobial effect sulfated galactan from Chaetomorpha aerea against the human bacterial pathogens such as Staphylococcus aureus, Salmonella enteretidis, P. aeruginosa, Enterococcus faecalis, Bacillus subtilis, Micrococcus luteus and Candida glabnata. It was suggested that the molecular mechanism of fucoidan on antibacterial activity is required to be further studied.…”
Section: Resultsmentioning
confidence: 88%
“…Similarly, Pierre et al, (2011) also reported the antimicrobial effect sulfated galactan from Chaetomorpha aerea against the human bacterial pathogens such as Staphylococcus aureus, Salmonella enteretidis, P. aeruginosa, Enterococcus faecalis, Bacillus subtilis, Micrococcus luteus and Candida glabnata. It was suggested that the molecular mechanism of fucoidan on antibacterial activity is required to be further studied.…”
Section: Resultsmentioning
confidence: 88%
“…longissima, L. japonica, Ecklonia cava, and Eisenia bicyclis have been evaluated for their bioactivities and attributed that to the high concentration of polysaccharides in these species which are known to have antimicrobial properties [14] [16] [34]. The more susceptibility of Gram-positive bac- teria to sulfated polysaccharides was due to the differences in their cell wall structure and their composition [35]- [37].…”
Section: Resultsmentioning
confidence: 99%
“…The biological properties of sulfated arabinogalactans extracted from the green algae such Chaetomorpha have been investigated. For instance, Pierre et al (2011) extracted and characterized an extracellular polysaccharide (a sulfated xyloarabinogalactan) from C. aerea with antibacterial activity against Staphylococcus aureus. Previous studies have found marked changes in the chemical constituents with change of seasons and environmental conditions (Manivannan et al 2009).…”
Section: Resultsmentioning
confidence: 99%